2016 Visionary Leader: Bob Dent. Issue 1 (January 2017) - Bredimus, Brandon "Kit"
Abstract : The following manuscript is the winning Richard Hader Visionary Leader 2016 entry submitted to Nursing Management in recognition of Dr. Bob Dent, DNP, MBA, RN, NEA-BC, CENP, FACHE, senior vice president, chief operating officer, and CNO for Midland Memorial Hospital in Midland, Tex. Dr. Dent was formally recognized for his achievements before the Keynote Address at Congress2016, November 8, in Las Vegas, Nev. There, he received the award, sponsored by Hackensack Meridian Health. Abstract : Get to know our newest winner, recognized in November at Nursing Management 's Congress2016 in Las Vegas.